Temporal and spatial variation of the metal-related oxidative potential of PM2.5 and its relation to PM2.5 mass and elemental composition. (February 2015) - Yang, Aileen; Hellack, Bryan; Leseman, Daan; Brunekreef, Bert; Kuhlbusch, Thomas A.J.; Cassee, Flemming R.; Hoek, Gerard; Janssen, Nicole A.H.
Abstract: Oxidative potential (OP) of particulate matter (PM) has been proposed as a more health relevant metric than PM mass. However, little is known about the temporal and spatial variation of OP, which is crucial if OP were to be used as an exposure metric in epidemiological studies. We studied OP on routinely collected PM2.5 samples (every 6th day) from three regional, five urban background, and three street sites over a one-year period across the Netherlands. OP was measured as the ability to generate hydroxyl radicals in the presence of hydrogen peroxide using the electron spin resonance (OP ESR ). OP ESR correlated poorly with PM2.5 mass both spatially (Spearman's r s  = 0.29) and temporally (median r s  = 0.34). The temporal correlations across sites for OP ESR were moderate (median r s  = 0.50) compared to PM2.5 (median r s  = 0.87), suggesting that exposure misclassification is higher when using OP ESR as an exposure metric in time series studies. Street/urban background and street/regional background ratios for OP ESR were 1.4 and 2.4 respectively; higher than for PM2.5 (ratio of 1.1 for both street/urban background and street/regional background). This large scale, nationwide study found that PM2.5 correlated poorly with OP ESR in space and time. Spatial contrasts were much larger for OP ESR than for PM2.5, which offers the possibility to use OP ESR to assess long-term exposure health effects. Highlights: The spatial and temporal variations of oxidative potential (OP ESR ) were assessed. OP ESR was 2.4 higher at street sites than corresponding regional background sites. Temporal correlations across and between different sites for OP ESR were moderate. Spatial contrasts were much larger for OP ESR than for PM2.5 . PM2.5 correlated poorly with OP ESR in space and time.